Building Self-Regulated Learning and Numeracy: An Experimental Study of the AIR Learning Model Based on Scientific Approach - Gunawan, Gunawan; Setyaningrum, Wahyu (Universitas Tidar, 2024)
This research aims to (1) determine the effectiveness of the Auditory, Intellectually, Repetition (AIR) learning model with a scientific approach to numeracy; (2) to determine the effectiveness of the AIR learning model with a scientific approach to self-regulated learning. This type of research is a pre-experiment with a one-group pretest-posttest design. The population in this research was all students in eighth grader at one of the junior high schools in Yogyakarta City, and one class was taken to bet the research class. Data collection techniques in this research used tests and non-tests. The test instruments used were pre-test and post-test questions on numeracy skills, and the non-test instruments used were self-regulated learning questionnaires and learning implementation observation sheets. Data analysis in this research consisted of a normality test with the Liliefors test, paired sample t-test, and N-Gain test. The research results show that (1) the AIR learning model with a scientific approach is effective for numeracy; (2) the AIR learning model with a scientific approach is not effective for self-regulated learning.